Upaya Istri Sebagai Wanita Karir Dalam Membentuk Keluarga Sakinah - Muniri, Akh. Syamsul Muniri; Ulfiyati, Nur Shofa (Prodi HKI IAI Miftahul Ulum Pamekasan, 2022)
A wife as a career woman has both positive and negative impacts on their household life. Therefore, forming a sakinah family for career women certainly has many challenges and obstacles. So far, the stigma that is often attached to society that women must look beautiful, look beautiful, look gentle and be at home with enough to take care of the household can be considered as psychological violence. Thus, career women's efforts to build family harmony so that they become a sakinah family, the strategy is to maintain commitments obtained from agreements between husband and wife and good communication between husband, wife and children. It is this commitment and communication that is important for career women, because women who work in the domestic sector and in the public sector have limited time and energy to carry out the two roles they have. Therefore, career women need support from the closest people around them so that life continues to run harmoniously.